2019
DOI: 10.1103/physrevlett.123.158003
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Local Dynamics in Matrix-Free Polymer Grafted Nanoparticles

Abstract: This is a copy of the published version, or version of record, available on the publisher's website. This version does not track changes, errata, or withdrawals on the publisher's site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 38 publications
7
33
0
2
Order By: Relevance
“…Therefore, QENS provides valuable insights into understanding relaxation processes in various PNCs systems. [6,[18][19][20][21] In P2VP/SiO 2 , our previous measurements showed that the spatial dependence of the segmental relaxation time was comparable between bulk and PNCs, implying spatially similar relaxations, despite the slower average relaxation rate. [11] Beyond the primary α-process, polymer segments can exhibit secondary relaxation such as the β-process attributed to nondiffusive relaxations or reorientations of segments or pendant groups in monomers.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Therefore, QENS provides valuable insights into understanding relaxation processes in various PNCs systems. [6,[18][19][20][21] In P2VP/SiO 2 , our previous measurements showed that the spatial dependence of the segmental relaxation time was comparable between bulk and PNCs, implying spatially similar relaxations, despite the slower average relaxation rate. [11] Beyond the primary α-process, polymer segments can exhibit secondary relaxation such as the β-process attributed to nondiffusive relaxations or reorientations of segments or pendant groups in monomers.…”
Section: Introductionmentioning
confidence: 87%
“…[1][2][3] For example, the addition of NPs to a polymer matrix can improve the mechanical properties of glassy and melt polymers [4,5] and enhance small molecule transport. [6,7] However, the microscopic origin of many of these altered macroscopic properties remains mechanistically unknown. In the specific case of mechanical and transport properties, segmental dynamics often underlie and dictate these properties in the melt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…尽管关于纳 米颗粒对聚合物纳米复合物体系的玻璃化相变温 度、黏性、弹性和力学增强的影响的实验研究越来 越多 [29][30][31][32][33] , 然而, 由于在聚合物纳米复合物的微观 行为和宏观性能之间缺乏确定的关系, 功能特定的 聚合物纳米复合材料的生产和商业化的发展存在很 大的障碍. 另一个困难是需要涉及的参数空间规模 巨大, 使得单纯通过实验进行筛选变得十分昂贵, 但 未来可以通过模拟帮助缩小在实验室中可能探索的 参数范围 [34][35][36][37][38][39][40][41][42] . 仅进行实验研究很难阐明在与纳米颗粒和聚 合物线团的大小相比拟的小尺度上纳米颗粒和聚 合物基质之间的相互作用机理, 从而由此得出纳米 尺度填料对相应的聚合物纳米复合材料微观行为 和宏观性能的影响 [43][44][45][46][47][48] [46] .…”
Section: 聚合物纳米复合材料与聚合物网络unclassified
“…然而, 该类仿生凝 胶材料的应用目前仍受到其自愈合进展缓慢的限 制 [26,34] . 最近, 实验研究表明纳米颗粒对聚合物链 的吸附能够被用来实现不同高分子链之间的强、快 030008-4 https://engine.scichina.com/doi/10.1360/SSPMA-2020-0427 速黏附, 以增强增多高分子链之间的非共价物理交 联 [27,37]…”
Section: 聚合物纳米复合材料与聚合物网络unclassified